Membangun Sistem Informasi Nagari Berbasis Website pada Nagari Salo Kec. Baso - Fanni Sukma; Yuhefizar; Ruzita Sumiati; Rino Sukma (ABEC Indonesia, 2022)
Nagari Salo is one of the villages in the Baso sub-district, Agam Regency. In preparing the Medium Term Development Plan (RPJM) for the Nagari, a website was created to make it easier for administrative services, to inform the activities, potential of the Nagari and the achievements of the Nagari Salo. This service activity aims to provide solutions to these problems, namely by building a village profile website and a village information system website to assist technology-based village services. To achieve the expected goals, this service is carried out in 5 stages, namely situation analysis, problem identification, determining the objectives and benefits of activities, problem solving plans and implementations, and website governance training so that the users are maximized. In addition, the team also facilitated building a Nagari online store website to help promote MSMEs in the Nagari. So that this service does not only help the nagari facilities in improving services to the community, it also improves the quality of human resources in managing the nagari towards a digital village.